A Parallel Computer Numerical Simulation Method Based on Coincident Coefficients. Issue 4 (April 2020) - Cui, Wenhui; Li, Yonghua; Sun, Zhenyu
Abstract: Analyze the coefficients relationship of 3rd order Runge-Kutta method and 4th order Runge-Kutta method, a parallel 4th order Runge-Kutta method based on consistent coefficient is proposed, the new parallel method can simultaneously satisfy the coefficients relationship both the 3rd order Runge-Kutta method and 4th order Runge-Kutta method with absolute stability region, it can be further parallel to lower order Runge-Kutta method. The method can be implemented in the multi-process MPI framework based on clusters. The method is applied to the numerical integral simulation of spacecraft orbit prediction, and the results of STK software are used asreference. The experimental results show that the accuracy of the parallel method is consistent with the serial method, and the computation speed is significantly higher than the serial method.